(untitled) (CAHIERS MAGELLANES-NS, 2024)
Development is a common and debated term in the contemporary world. It is perceived differently within various perspectives. Though development is perceived to be solely economic activities it has various facets ranging from social, political, cultural and demographical and environment. However, the term is often used to refer activities solely economic and infrastructural connotations. Economic development bring many changes to the lives of people and it also degrades the lives of certain group of people in society, mostly the under privileged groups. Such development though comes as boon to a section of people it also posed as threats to livelihoods, social, cultural and political existence of some groups. Development intervention by the state in the form of roads, railways and hydro-power etc. that are expected to bring about quality changes in lives of people in recent times has been witnessing mass protests from many communities in various part India. The Bogibeel Bridge has caused vast land acquisition forcing displacement in Dhemaji district of Assam. It is alleged, the benefit gained from the projects are less than the impacts to the live and livelihood of the already poor agricultural communities in the project areas.